Paul Celan's Linguistic Mysticism - Shira Wolosky (Studies in 20th & 21st Century Literature, 1986)
Paul Celan's works often seem to grant to language an autonomy that isolates poetic from extra-poetic concerns, including religious ones. The status of language in Celan, however, should be assessed in the context of its status within Judaic mysticism. While the importance of mysticism for Celan has been recognized, the degree to which Judaic mysticism differs from other mystical traditions has been less so. This is especially true with regard to the place given to language in the Kabbalah, and the structures and assumptions that its conception of language implies. Of importance to Celan, for example, is the Kabbalistic notion that language is the very substance constituting creation. By examining such Judaic mystical motifs in several Celan poems, this essay attempts to show that Celan's preoccupation with language does not entail a withdrawal into a self-enclosed linguistic world, and that ultimately his religious concerns are intimately involved with his aesthetic ones.
Keywords: Paul Celan; German Literature; religious; religion; Judaic mystics; Kabbalah; creation; language; poetry; linguistics; aesthetics